Comprehensive optimization of passenger trains operation based on an automated system for managing the profitability of passenger traffic - G. L. Venediktov; V. M. Kochetkov (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
The article is devoted to solving the problem of optimizing the tariff policy, which is relevant for the passenger complex, with the most rational use of the rolling stock. Principles of economic and mathematical modeling are presented in order to determine the optimal number of cars in passenger trains and prices for travel in a single calculation process called complex optimization. Developed models make it possible to form optimal train schemes in accordance with the predicted demand, balancing supply and demand for transportation, which, in turn, radically increases its economic efficiency. Simultaneously with finding the optimal schemes by the method of complex optimization, such fares are determined at which the balance of supply and demand is achieved with the maximum possible economic effect. The article discusses the analytical models of passenger demand, the principles of implementation of the complex optimization procedure, the problems of forecasting passenger demand and the features of calculating the forecast of demand for the example of train No. 17/18 “Karelia” on the Petrozavodsk—Moscow route, and also offers a solution to the problem of determining the optimal prices and train schemes. On the example of real data of the operation of this train, the effectiveness of the automated system for managing the profitability of passenger traffic, created on the basis of complex optimization algorithms, was evaluated. It is shown that the developed analytical models of passenger demand allow solving optimization problems that increase the efficiency of automated control systems for the economic indicators of the transportation process, and the multi-model forecasting system provides satisfactory accuracy with a high level of forecast detail. Due to the fact that the level of expenses for train journeys radically affects the result of optimization of the transportation process with variable train schemes, the adopted optimization criterion takes into account both income and transportation costs. The results of calculations are presented showing that the complex optimization procedure for the “Karelia” train could give a significant additional financial result.